Parental deployment and distress, and adolescent disordered eating in prevention‐seeking military dependents. Issue 2 (8th October 2019) - Higgins Neyland, M. K.; Shank, Lisa M.; Burke, Natasha L.; Schvey, Natasha A.; Pine, Abigail; Quattlebaum, Mary; Leu, William; Gillmore, Dakota; Morettini, Alexandria; Wilfley, Denise E.; Stephens, Mark; Sbrocco, Tracy; et al.
Abstract: Objective: Parental military deployment can lead to stress in the family system due to concerns about the deployed service‐member's safety and increased responsibilities for those not deployed. Parent‐related stress can impact adolescent disordered eating. Given the important role that stress plays in disordered eating and obesity, it is crucial to understand the impacts of unique stressors to which vulnerable populations are exposed. Method: We studied 126 adolescent (14.3 ± 1.6 years; 59.5% girls; 44.4% non‐Hispanic White; BMI‐ z, 1.91 ± .39) military dependents prior to entering an obesity and binge‐eating disorder prevention trial. The Eating Disorder Examination was used to assess adolescent disordered eating. Parents self‐reported their own distress and family deployment history that occurred during the adolescent's lifetime. Results: Parental distress interacted with frequency of parental deployments such that for those with high parental distress, more frequent deployment was associated with greater adolescent shape and weight concerns ( β = .21, p = .012) and global eating pathology ( β = .18, p = .024). Discussion: In this hypothesis‐generating study, the combination of number of deployments and parental distress may be associated with disordered eating among adolescent military dependents seeking prevention of binge‐eating disorder and adult obesity. If these preliminary findings are supported longitudinally, interventions to reduce parental stress related to deployment may be warranted to reduce disordered eating in adolescent dependents.